Suppression of optineurin impairs the progression of hepatocellular carcinoma through regulating mitophagy. (18th February 2021) - Inokuchi, Shoichi; Yoshizumi, Tomoharu; Toshima, Takeo; Itoh, Shinji; Yugawa, Kyohei; Harada, Noboru; Mori, Hiroyuki; Fukuhara, Takasuke; Matsuura, Yoshiharu; Mori, Masaki
Abstract: Autophagy removes damaged organelles to inhibit malignant transformation during tumor initiation. Once a cancer matures, it uses the autophagic pathway as an energy source. Optineurin (OPTN) is an autophagy adaptor protein that recruits microtubule‐associated protein 1 light chain 3, an autophagosome marker, to the autophagosome. Despite studies of the relation between cancer progression and autophagy adaptor proteins, there are no reports to our knowledge of a correlation between hepatocellular carcinoma (HCC) and OPTN. We aimed here to investigate the effects of OPTN expression on HCC progression through autophagy. Immunohistochemistry was used to measure the OPTN expression in the tissues of 141 Japanese patients with HCC. The effects of OPTN expression on HCC progression and mitophagy were assessed using an OPTN knockout (KO) cell line in vitro. We used this KO cell line to establish and exploit a mouse model of HCC to determine the effects of OPTN expression on tumor progression. Immunohistochemical analysis showed that patients with elevated expression of OPTN experienced shorter overall survival (OS) and recurrence‐free survival (RFS). OPTN KO cells proliferated relatively slower versus wild‐type (WT) cells in vitro. Western blot analysis showed that mitophagy was suppressed in OPTN KO cells, and ATP synthesis and beta‐oxidation were reduced. The mouse model of HCC showed that OPTN KO cells formed smaller tumors versus WT cells less 10 weeks after implantation. Overall, the present findings suggest that OPTN is a key mediator of mitophagy that contributes to HCC progression through mitochondrial energy production. Abstract : Optineurin (OPTN) is required for mitophagic activity as shown by the significant association of OPTN expression levels with mitochondrial beta‐oxidation. Moreover, elevated levels of OPTN were associated with worse prognosis of HCC. Our findings provide a foundation for determining the roles of other autophagy adaptor proteins in the pathogenesis and progression of HCC as well as in other cancers.